â€œVisit My Stallâ€, A Game For Learning Indonesian as a Foreign Language (BIPA) - Zulfa, Puspa Fortuna; Triyono, Sulis (PAROLE: Journal of Linguistics and Education, 2018)
Essentially, learning Indonesian is the same as learning other foreign languages for the foreigners, and it uses the same methods for teaching and learning process. The tutor of that learning Indonesian for the foreigners (BIPA) must choose the appropriate methods for making teaching and learning process runs well and interesting. This paper is written based on the literature which aims at promoting a game, Visit My Stall, game for learning Indonesian as a foreign language. This paper also tries to show the explanation about this game, how to implement it, roles of the teacher and learners, as well as the assessment and the advantages offered. This game is created based on the principles of Communicative Language Teaching and Cooperative Learning in which learners are given the opportunities for cooperating with their group actively and interacting by exchanging their ideas to solve the problems in the form of tasks given by the teacher by means for achieving the same goals of each group. This game is not only to improve learnersâ€™ speaking skill in Indonesian, but also to motivate them when the learning process takes place. Thus, learning Indonesian for the foreigners will be an exciting and enjoyable activity for them.